Beyond the Ballot: A Comparative Analysis of Political Microtargeting Practices and Regulations in Kenya and Nigeria (Journal of Intellectual Property and Information Technology Law (JIPIT), 2023)
Technological advancements have significantly impacted the political world. Unlike the traditional means of conducting campaigns, technology makes it possible to conduct data-driven campaigns on a larger scale and with high levels of specificity. For political parties, better clarity leads to hyper-individualized communication in a process known as microtargeting. Critics argue that political microtargeting can directly manipulate and suppress voters, exacerbate polarization, perpetuate misinformation, and indirectly lead to long-term effects by encouraging political parties to ignore individuals whom they deem unlikely to vote or those who are digitally excluded. This paper studies political microtargeting in Kenya and Nigeria because of data-driven campaigns that have been observed in these jurisdictions in the past and due to the increased reliance on social media platforms that political actors are utilizing to influence voters. It argues that political microtargeting is an issue of concern and therefore, using Kenya and Nigeria, it pushes the agenda that countries in the Global South should implement policies and regulations to curtail the negative impact of the practice. To examine the extent of political microtargeting in both Kenya and Nigeria, this paper employs a multi-phase approach that involves an analysis of paid Facebook advertisements in both countries during the past election periods.